Analysis of “A Gospel According to Joan”: Short Story as a Way in Understanding Fiction Literature - Wan Angelica Agustina; Ni Luh Putu Krisnawati; I Made Suastra (CV. Ulil Albab Corp, 2023)
This study aims to analyze the intrinsic and extrinsic structures contained in the short story